Evaluation of the Potential Accuracy of Correlation Extreme Navigation Systems of Low-Altitude Mobile Robots - Tantsiura, A.; Kolomiets, D.; Tabakova, I.; Hannoshyna, I.; Serdiuk, N.; Yelieazarov, O.; Voichenko, T. (My University, 2019)
The sight surface (SS) results for the generalized model image development of the correlation-extreme navigation systems (KENS) of mobile robots (MR) in the informative parameter step difference form used in the system are presented. The generalized telegraph process model usage possibility of the radiation emitter image in a wide MR spectral range is substantiated. To assess the KENS accuracy potential for this model type image the relations are obtained. The potential KENS positioning accuracy assessment for typical model conditions of MR usage is carried out. The estimates are made for the informative parameter used in radiometric navigation systems, which can be similarly obtained for other types of informative parameters.
Keywords: mobile robot; extreme correlation navigation system; generalized telegraph process; potential accuracy